Asthma Management at Discharge from the Emergency Department: A Descriptive Study. Issue 4 (3rd June 2005) - Gervais, Pascale; Larouche, Isabelle; Blais, Lucie; Fillion, Anne; Beauchesne, Marie-France
Abstract : BACKGROUND: The management of asthma remains suboptimal despite the publication of Canadian asthma guidelines in 1999. OBJECTIVES AND METHODS: A descriptive study was conducted to estimate the proportion of patients admitted to the emergency department (ED) for an asthma exacerbation who received a management plan at discharge that was in accordance with seven criteria stated in the Canadian asthma guidelines. The present study took place in two tertiary care hospitals in Montreal, Quebec. RESULTS: A total of 37 patients were enrolled. Three (8%) patients received a management plan at discharge that was in accordance with all seven criteria. Inhaled corticosteroids and oral corticosteroids were prescribed at discharge for 29 (78%) and 35 (95%) patients, respectively. Minimal asthma education was provided for 29 (78%) patients and a medical follow-up was recommended to 22 (60%) patients. Airflow obstruction was evaluated at discharge for only 20 (54%) patients. CONCLUSION: Overall, asthma management at discharge from the ED was generally not in accordance with the 1999 Canadian asthma guidelines. A standardized management plan should be implemented in the ED to improve the care of patients with asthma exacerbations.